Excellence for all : how a new breed of reformers is transforming America's public schools - Schneider, Jack (Writer on education) (Vanderbilt University Press, 2011)
By the early twentyfirst century, a startling consensus had emerged about the overall aim of American school reform. In an era of political discord, and in a field historically known for contentiousness, the notion of promoting educational excellence for all students was a distinct point of bipartisan agreement. Shaped by a corps of entrepreneurial reformers intent on finding "what works" and taking it to scale, this hybrid vision won over the nation's most ambitious and wellresourced policy leaders at foundations and nonprofits, in state and federal government, and in urban school districts from coast to coast. "Excellence for all" might, at first glance, appear to be nothing more than a rhetorical flourish. Who, after all, would oppose the idea of a great education for every student? Yet it is hardly a throwaway phrase. Rather, it represents a surprising fusion of educational policy approaches that had been in tense opposition throughout the twentieth centurythose on the right favoring social efficiency, and those on the left supporting social justice. This book seeks to understand why the "excellence for all" vision took hold at the time it did, unpacks the particular beliefs and assumptions embedded in it, and details the often informal coalition building that produced this period of consensus. Examining the nation's largest urban school districts (Los Angeles, Chicago, and New York), the author details three major reform efforts in chapters titled "The Right Space: The Small Schools Movement"; "The Right Teachers: Teach for America"; and "The Right Curriculum: Expanding Advanced Placement."